Environmental conflicts in the microrregião de Viçosa-MG: the conflict between environmental legislation and farm workers and the excess of the penalty on small cases of violations of environmental legislation - Carneiro, Eder Jurandir; Assis, Mauro F. C. (Centro de Historia Argentina y Americana, 2011)
The research presented in this article aims to identify and to analyze the cases of environmental conflicts in the microrregião de Viçosa, Minas Gerais, Brasil. For this were performed data surveys were conducted in the archives of the Ministério Público regarding the municipalities of microrregião in study and a workshop with various social movements of the mesorregião da Zona da Mata. From this survey on we check the conflict established between environmental legislation and farm workers, and also the concentration of the penalty on small cases of violations of environmental legislation. Thus, we conclude that to think about environmental conflicts is require the recognition of inequalities of power and the different types of knowledge and rationalities involved in the appropriation of natural resources by society.